2019
DOI: 10.1186/s13041-019-0453-4
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic effects of Formononetin in an inflammatory pain mouse model

Abstract: Chronic pain is commonly accompanied with anxiety disorder, which complicates treatment. In this study, we investigated the analgesic and anxiolytic effects of Formononetin (FMNT), an active component of traditional Chinese medicine red clover ( Trifolium pratense L.) that is capable of protecting neurons from N-methyl-D-aspartate (NMDA)-evoked excitotoxic injury, on mice suffering from complete Freund’s adjuvant (CFA)-induced chronic inflammatory pain. The results show that FMNT adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 68 publications
1
29
0
Order By: Relevance
“…Ionotropic glutamate receptors include AMPAR and NMDAR, such as GluA1, GluA2, GluN2A, and GluN2B, which play critical roles in regulating synaptic neurotransmission and plasticity as well as in anxiety [39]. In this study, CFA resulted in increased expression of GluA1, GluN2A, GluN2B, and PSD95, a postsynaptic anchor protein that binds to AMPA and NMDA receptors [40]. Treatment with SP down-regulated GluA1 and PSD95, but had no obvious effect on the levels of GluN2A and GluN2B.…”
Section: Discussionmentioning
confidence: 70%
“…Ionotropic glutamate receptors include AMPAR and NMDAR, such as GluA1, GluA2, GluN2A, and GluN2B, which play critical roles in regulating synaptic neurotransmission and plasticity as well as in anxiety [39]. In this study, CFA resulted in increased expression of GluA1, GluN2A, GluN2B, and PSD95, a postsynaptic anchor protein that binds to AMPA and NMDA receptors [40]. Treatment with SP down-regulated GluA1 and PSD95, but had no obvious effect on the levels of GluN2A and GluN2B.…”
Section: Discussionmentioning
confidence: 70%
“…We established OVA-induced murine model of allergic asthma and set doses of formononetin and dexamethasone based on previous studies with minor modification (Wang et al, 2016;Campa et al, 2018;Li et al, 2018;Luo et al, 2018;Wang X. S. et al, 2019). Sixty mice were randomly assigned to six groups (10 mice/group) as follows: normal control group; asthma group; asthma + formononetin 10 mg/kg group (Winherb Medical Science Co. Ltd, Shanghai, China); asthma + formononetin 20 mg/kg group; asthma + formononetin 40 mg/kg group; asthma + dexamethasone 2 mg/kg group.…”
Section: Ova−induced Asthmatic Model and Treatmentmentioning
confidence: 99%
“…FMT has a bioavailability of 21.8% and shows different absorption in all gastrointestinal segments ( Luo et al., 2018 ). An increasing body of evidence suggests that FMT exerts notable anti-inflammatory, anti-allergic, antioxidant, anti-hepatic steatosis, antiproliferative, and anticancer effects in vitro and animal models of many disease ( Wang et al., 2012 ; Xu and An, 2017 ; Fei et al., 2018 ; Li et al., 2018 ; Ong et al., 2019 ; Wang X. S. et al., 2019 ). Some reports demonstrate that FMT has neuroprotective effect in LPS-stimulated BV2 microglia and high-fat diet-induced cognitive disorder mice ( El-Bakoush and Olajide, 2018 ; Fu et al., 2019 ; Wang Y. et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another flavonoid known to have anxiolytic effects is formononetin, an active metabolite of traditional Chinese medicine red clover (Trifolium pratense L.). Wang et al [47] observed that administering 25 mg/kg of this metabolite to male mice once daily for 8 days blocked the anxiogenic effect on the open field test (OFT) produced by administering Freund's complete adjuvant (CFA), reduced the time spent and distance traveled in the central area, and decreased the time spent in the open arms of EPM [47]. Formononetin did not modify behavior compared to the control group on either test, indicating that it demonstrated an anxiolytic effect.…”
Section: Flavonoids With Anxiolytic Effectsmentioning
confidence: 99%
“…However, it seems that these results should be understood as a neuroprotective effect more than an anxiolytic one, at least under those study conditions. The notion of a neuroprotector effect is supported by the fact that the study found that formononetin attenuated inflammation and neuronal hyperexcitability by inhibiting NMDA receptors and the CREB signaling pathway in the basolateral amygdala (BLA) [47].…”
Section: Flavonoids With Anxiolytic Effectsmentioning
confidence: 99%